The Middle and Late Woodland transition in southern Ontario: smoking culture as an index of social change in the context of sedentism - Zepf, Lena (My University, 2014)
This thesis puts forward a unique perspective for how we can view changes in the context of sedentism, specifically with regard to the Middle and Late Woodland periods (ca. 400 B.C. – A.D. 1650) in southern Ontario. The transition to a more sedentary way of life leads to significant socio-economic changes in settlement type, subsistence, demography, architecture, and material culture, and acts as an incentive for change as it pertains to ideological transformations. In this thesis I concentrate on how changing ways of living impacted people’s ideology and related practices, focusing on the social habit of smoking, and its related material culture pre and post-sedentism in southern Ontario. I suggest that the changes witnessed in this practice (and associated paraphernalia) are reflective of a means of social group maintenance, and by extent a different mechanism of how societies regulated themselves. My study further examines the role smoking pipes had for group and individual recreational use, alongside group communal practices. I propose that more pipes per site signify daily use, reflecting a shift away from the pre-sedentary communal practice of smoking led by ritual specialists, to a post-sedentary individual and occasional group experience. Moreover, I argue for a link between smoking, social relationships, and the promotion of social solidarity. The stimulus for certain practices, and the structure of the socio-cultural system within which they occur, is significant for they are interwoven into all aspects of society. The aim of this thesis is to add to our perception of change and transformation during the Middle and Late Woodland periods of southern Ontario, while providing a unique perspective for understanding socio-cultural transformation in the context of sedentism more generally.
Keywords: Ontario archaeology; smoking pipes